Mechanical Properties and Performance of CNT–Reinforced Mortars (CEM II/B–L and CEM I) for Crack Bridging and Protective Coating Applications - Nikolaos Chousidis (Buildings, 2025)
Cement–based mortars are essential in both modern construction and heritage conservation, where balancing mechanical strength with material compatibility is crucial. Mortars containing ––binders with low hydraulic activity, such as CEM II/B–L, often exhibit increased porosity and diminished strength, limiting their suitability for structurally demanding applications. This study investigates the potential of multiwalled carbon nanotubes (MWCNTs) to enhance the mechanical and microstructural properties of mortars formulated with both CEM II/B–L and CEM I binders. The influence of CNT incorporation was systematically assessed through compressive and flexural strength tests, vacuum saturation tests, mercury intrusion porosimetry (MIP), scanning electron microscopy (SEM), and differential thermal analysis (DTA). The results demonstrate significant mechanical improvements attributable to nanoscale mechanisms including crack bridging, pore–filling, and stress redistribution. Microstructural characterization revealed a refined pore network, increased densification of the matrix, and morphological modifications of hydration products. These findings underscore the effectiveness of CNT reinforcement in cementitious matrices and highlight the critical role of binder composition in influencing these effects. This work advances the development of high–performance mortar systems, optimized for enhanced structural integrity and long–term durability.